2018
DOI: 10.1107/s205979831800952x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of an essential high-temperature requirement protein HtrA1 (Rv1223) from Mycobacterium tuberculosis reveals its unique features

Abstract: High-temperature requirement A (HtrA) proteins, which are members of the heat-shock-induced serine protease family, are involved in extracytoplasmic protein quality control and bacterial survival strategies under stress conditions, and are associated with the virulence of several pathogens; they are therefore major drug targets. Mycobacterium tuberculosis possesses three putative HtrAs: HtrA1 (Rv1223), HtrA2 (Rv0983) and HtrA3 (Rv0125). Each has a cytoplasmic region, a transmembrane helix and a periplasmic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…While the expression constructs for the periplasmic domain are broadly similar, the authors reported that this protein was a trimer in solution. Owing to issues with autoproteolysis and/or degradation, the structure that was determined was that of an active-site mutant (Singh et al, 2018). The structure of the active enzyme described here at higher resolution (1.83 Å ) also reveals a few differences from the previous report.…”
Section: Quaternary Association Of M Tuberculosis Dtm Htramentioning
confidence: 69%
See 1 more Smart Citation
“…While the expression constructs for the periplasmic domain are broadly similar, the authors reported that this protein was a trimer in solution. Owing to issues with autoproteolysis and/or degradation, the structure that was determined was that of an active-site mutant (Singh et al, 2018). The structure of the active enzyme described here at higher resolution (1.83 Å ) also reveals a few differences from the previous report.…”
Section: Quaternary Association Of M Tuberculosis Dtm Htramentioning
confidence: 69%
“…While this manuscript was being compiled for peer review, the structure of M. tuberculosis ÁTM HtrA was reported (Singh et al, 2018). In their manuscript, Singh and coworkers described the crystal structure of M. tuberculosis HtrA determined at 2.7 Å resolution (PDB entry 5zvj).…”
Section: Quaternary Association Of M Tuberculosis Dtm Htramentioning
confidence: 99%
“…The molecular analysis of different HtrA serine proteases of other pathogenic bacteria via multiple sequence alignment (MSA) revealed a sequence similarity, especially in the functional protease and PDZ domains, as reviewed more extensively elsewhere (Backert et al, 2018;Boehm et al, 2018;Singh et al, 2018). They are widely distributed in many bacterial species such as Escherichia coli, Legionella fallonii, Thermotoga maritima, and Mycobacterium tuberculosis (Kim et al, 2003;Bai et al, 2011;Malet et al, 2012;Cortes et al, 2013;Chang, 2016;Singh et al, 2018).…”
Section: Molecular Characterization and Structure Of Serine Protease-like/chaperone Htramentioning
confidence: 99%
“…Bacterial HtrA is a heat-shock-induced serine protease that displays a multifunctional role like protein quality control and bacterial survival under different stress conditions such as oxidative and heat stress ( Sebert et al., 2002 ; Singh et al., 2018 ). For instance, HtrA protease in Lactococcus is considered as a housekeeping protease ( Poquet et al., 2000 ), while in other bacteria, HtrA prevents the cell from the cytotoxicity of misfolded proteins by refolding or degrading them ( Clausen et al., 2002 ; Zarzecka et al., 2019 ).…”
Section: Molecular Characterization and Structure Of Serine Protease-like/chaperone Htramentioning
confidence: 99%
See 1 more Smart Citation